Location of injected polymethylmethacrylate microspheres influences the onset of late adverse effects: an experimental and histopathologic study - Jesus LH; Hildebr; LC; Martins MD; Rosa FM; Danilevicz CK; Sant'Ana Filho M (Dove Medical Press, 2015)
Luciano Henrique de Jesus, Laura de Campos Hildebrand, Manoela Domingues Martins, Francinne Miranda da Rosa, Chris Krebs Danilevicz, Manoel Sant'Ana Filho Department of Oral Pathology, School of Dentistry, Universidade Federal do Rio Grande do Sul, Porto Alegre, RS, Brazil Abstract: Polymethylmethacrylate (PMMA) has been widely used in the correction of wrinkles because of its long-lasting cosmetic improvements. However, side effects and complications may occur, and its clinical appearance on the oral mucosa can be similar to that of inflammatory or neoplastic disease. The aim of this research was to compare the clinical and histopathologic responses to PMMA injected by two different methods. Twenty-two rats received an injection of PMMA using the tunneling technique (gold standard), with subcutaneous deposition of the filler in the face, or a variation of the technique with transcutaneous submucosal deposition of the filler in the cheek. The tissue reaction was analyzed clinically every 24 hours during the first week, then once a week for the following 3 months. Histologic evaluation was based on the local inflammatory response to the filler. No clinical changes were observed during the initial evaluation period (0–14 days). After 14 days, only the submucosal group showed extra-oral enlargement (n=4, 18.2%). Histopathologic analysis revealed nodule formation in four animals (18.2%) in the submucosal group, with no nodules observed in the subcutaneous group. The data obtained in this study demonstrate that the technique used to deliver the filler may influence the risk of adverse reactions. Keywords: dermal filler, polymethylmethacrylate, adverse reactions